Highly-efficient synthesis of biogenic selenium nanoparticles by Bacillus paramycoides and their antibacterial and antioxidant activities - Liu, Pei; Long, Haiyu; Cheng, Han; Liang, Mengdi; Liu, Zhengwei; Han, Zhenlian; Guo, Zhen; Shi, Hao; Sun, Min; He, Shuai (Frontiers in Bioengineering and Biotechnology, 2023)
Bacillus species are known for their ability to produce nanoparticles with various potential applications. In this study, we present a facile approach for the green synthesis of selenium nanoparticles (Se NPs) using the biogenic selenate-reducing bacterium Bacillus paramycoides 24522. We optimized the growth conditions and sodium selenite reduction efficiency (SSRE) of B. paramycoides 24522 using a response surface approach. Se NPs were synthesized by reducing selenite ions with B. paramycoides 24522 at 37 °C, pH 6, and 140 r/min, resulting in stable red-colored Se NPs and maximal SSRE (99.12%). The synthesized Se NPs demonstrated lethality against Staphylococcus aureus and Escherichia coli with MICs of 400 μg/mL and 600 μg/mL, and MBCs of 600 μg/mL and 800 μg/mL, respectively, indicating the potential of Se NPs as antibacterial agents. Furthermore, the Se NPs showed promising antioxidant capabilities through scavenging DPPH radicals and reducing power. This study highlights the environmentally friendly production of Se NPs using B. paramycoides 24522 and their possible applications in addressing selenium pollution, as well as in the fields of environment and biotechnology.